El carácter prociclico de la política fiscal: notas sobre la ley de prudcencia y transparencia fiscal - Jiménez, Félix (2003)
This paper is aimed to describe the basic limitations of the current fiscal responsibility lawto deal with the economic recession due to its pro cyclical character. Section 2 contains atheoretical model, which relates the aggregate demand to the pro cyclical fiscal rule. Two casesof static comparative analysis are developed in section 3: external shock and monetary policyshock; and the possibility of a fiscal and monetary policy mix to reactivate the economy is alsoanalyzed. In section 4 contains the empirical evidence of the fiscal policy character in the lastdecade. Finally, a brief review on the application of the fiscal rules experiences is developed inthe last section, and some changes on the law are suggested in order to make it more credible andefficient for public budget management.